2019
DOI: 10.1111/jocd.13041
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal permeation effect of collagen hydrolysates of deer sinew on mouse skin, ex vitro, and antioxidant activity, increased type I collagen secretion of percutaneous proteins in NIH/3T3 cells

Abstract: Background:The collagen hydrolysates as a cosmetic material have already been wide application. At present, few studies concern with transdermal behavior of collagen hydrolysates in vitro.Objective: Deer sinew contains rich collagen with a content of 82.12%. Thus, this article mainly studies the transdermal effect of collagen hydrolysates of deer sinew (DSCH) on mouse skin, ex vitro, and to explore skincare protection of percutaneous proteins. Methods: Collagen hydrolysates of deer sinew were extracted by 0.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…Similar studies showed that an antioxidant peptide of 1673 Da isolated from frog skin secretions had the ability to penetrate the cell membrane of HaCaT keratinocytes and to stimulate in vitro migration mechanisms, but also to prevent skin inflammation and photoaging of UVB irradiated mice skin by topical administration [ 39 ]. Collagen peptides from deer tendon with MW 5–13 kDa were able to penetrate the mice skin, unlike native collagen, and promoted cell proliferation [ 40 ]. In vivo studies reported that tilapia scales collagen peptides of 3.5–4.5 kDa showed better penetration of mice stratum corneum than smaller peptides (1.3 kDa) and improved women skin moisture and elasticity [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar studies showed that an antioxidant peptide of 1673 Da isolated from frog skin secretions had the ability to penetrate the cell membrane of HaCaT keratinocytes and to stimulate in vitro migration mechanisms, but also to prevent skin inflammation and photoaging of UVB irradiated mice skin by topical administration [ 39 ]. Collagen peptides from deer tendon with MW 5–13 kDa were able to penetrate the mice skin, unlike native collagen, and promoted cell proliferation [ 40 ]. In vivo studies reported that tilapia scales collagen peptides of 3.5–4.5 kDa showed better penetration of mice stratum corneum than smaller peptides (1.3 kDa) and improved women skin moisture and elasticity [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhang and co-workers conducted an experimental setup to assess the transdermal permeation effect of HC from deer sinew on mouse skin as well as the skincare protection of percutaneous proteins [39,40]. They found that approximately 8.0% of HC with a molecular weight between 5 and 13 kDa could penetrate the skin.…”
Section: Transdermal Penetration Of Hc On the Skinmentioning
confidence: 99%
“…The novel hydrolysate is found rich in X-Hype-Gly tripeptides that show an increase in their degree of mineralization to achieve high differentiation for mouse MC3T3-E1 pre-osteoblasts [ 58 ]. Recently, Zhang et al proposed a novel deer sinew collagen hydrolysate for dermal (skin) use [ 59 ]. The percutaneous proteins from novel collagen induce significant cell proliferation of NIH3T3 cells.…”
Section: Collagen Typementioning
confidence: 99%